Ecological and functional research into microbiomes for targeted phenolic removal in anoxic carbon-based fluidized bed reactor (CBFBR) treating coal pyrolysis wastewater (CPW). (July 2020) - Zheng, Mengqi; Shi, Jingxin; Xu, Chunyan; Ma, Wencheng; Zhang, Zhengwen; Zhu, Hao; Han, Hongjun
Graphical abstract: Highlights: CBFBRs enhanced degradation performance for targeted phenols. Brachymonas genus provided microbial basis for robust performance of CBFBRs. Geobacter assisted impact resistance by enhancing interspecific electron transfer. Anaerobic pathway accounted for demethylation procedure. Aerobic pathway dominated phenolic ring-cleavage process. Abstract: Powdered activated carbon (PAC), lignite activated coke (LAC) and Fe-C carriers were applied to enhance CBFBRs to degrade targeted phenolics. In start-up stage, PAC and LAC equipped CBFBRs with higher environment adaptability and phenolic degradation capacity for phenol (>96%), p-cresol (>91%) and 3, 5-dimethylphenol (>84%) in comparison to Fe-C carrier. In recovery stage, the superior performance was also identified for CBFBRs in basis of PAC and LAC than Fe-C-based reactor. However, the Fe-C carrier assisted CBFBR with more stable degradation performance under impact loading. By comparing microbiomes, significantly enriched Brachymonas (54.80%–68.81%) in CBFBRs exerted primary role for phenolic degradation, and positively contributed to microbial network. Meanwhile, Geobacter in Fe-C-based reactor induced excellent impact resistance by enhancing interspecific electron transfer among microbes. Furthermore, the investigation on functional genes related to phenolic degradation revealed that anaerobic pathway accounted for demethylation procedure, while aerobic pathways dominated the phenolic ring-cleavage process.